Activation of PERK/eIF2α/ATF4 signaling inhibits ERα expression in breast cancer - Yuanli Wu; Gang Wang; Ruixue Yang; Duanfang Zhou; Qingjuan Chen; Qiuya Wu; Bo Chen; Lie Yuan; Na Qu; Hongmei Wang; Moustapha Hassan; Ying Zhao; et al. (Neoplasia: An International Journal for Oncology Research)
Approximately 70–80% of breast cancers rely on estrogen receptor alpha (ERα) for growth. The unfolded protein response (UPR), a cellular response to endoplasmic reticulum stress (ERS), is an important process crucial for oncogenic transformation. The effect of ERS on ERα expression and signaling remains incompletely elucidated. Here, we focused on the regulatory mechanisms of ERS on ERα expression in ER-positive breast cancer (ER+ BC). Our results demonstrate that ERα protein and mRNA levels in ER+ BC cells are considerably reduced by the ERS inducers thapsigargin (TG) and brefeldin A (BFA) via the PERK/eIF2α/ATF4 signaling pathway. ChIP-qPCR and luciferase reporter gene analysis revealed that ERS induction facilitated ATF4 binding to the ESR1 (the gene encoding ERα) promoter region, thereby suppressing ESR1 promoter activity and inhibiting ERα expression. Furthermore, selective activation of PERK signaling or ATF4 overexpression attenuated ERα expression and tumor cell growth both in vitro and in vivo. In conclusion, our results demonstrate that ERS suppresses ERα expression transcriptionally via the PERK/eIF2α/ATF4 signaling. Our study provides insights into the treatment of ER+ BC by targeting ERα signaling through selective activation of the PERK branch of the UPR.